Case of Pulmonary Extramedullary Hematopoiesis Responding to Ruxolitinib. (2022) - Fujimoto, Ayumi; Hamaguchi, Shunichi; Suzuki, Ritsuro
Abstract: We report a case of 43-year-old woman diagnosed with essential thrombocythemia in 1992. She was diagnosed with secondary myelofibrosis in 2011. Later, she suffered mild dyspnea, which gradually worsened. She was admitted to our hospital to evaluate the cause in 2014. Chest computed tomography showed ground-glass opacity (GGO) in the lungs. A lung biopsy revealed various hematopoietic cells, including abnormal megakaryocytes, infiltrating the alveolar septum, suggesting pulmonary extramedullary hematopoiesis. She was successfully treated by ruxolitinib and her disease is well controlled for more than 7 years. To keep this phenomenon in mind when see the patients with dyspnea is important.